Surface effects on the wave propagation in composites with random dispersive parallel cylindrical nanofibers - Kong, Z.; Qiang, F.W.; Wei, P.J.; Tang, Q. (Archives of Mechanics, 2015)
The propagation of elastic waves in composites with randomly distributed parallel cylindrical nanofibers is studied. The non-classical boundary conditions on the surface of nanofibers are derived by using the surface elasticity theory. The scattering waves from an individual nanofiber are obtained by the plane-wave expansion method. These scattering waves from all nanofibers are summed up to obtain the multiple-scattering waves. The effective propagation constants (speed and attenuation) of coherent waves and the associated effective dynamical moduli of composites are evaluated numerically. Based on these numerical results, the influences of the surface effects on the effective dynamical properties of composites are discussed.